Sistem Informasi Administrasi Pelaporan Realisasi SKPD Berbasis Web Pada Bappeda Kabupaten Kuburaya - Panny Agustia Rahayuningsih; Fradinata Fradinata (Fakultas Teknik Universitas Hamzanwadi, 2022)
Each Regional Apparatus Work Unit (SKPD) must report the use of the budget or realization report to BAPPEDA. Each SKPD officer submits a realization report to the Secretariat. If an error occurs in the preparation of the realization report, the wrong SKPD will be informed again and must re-create and repeat the administration process for reporting realization. This is deemed ineffective, because each SKPD must come to the office only to submit a realization report and also charge officers who fill in the realization data for each SKPD. Therefore, this writing contains research to solve the problems faced by BAPPEDA Kubu Raya Regency by building a web-based SKPD realization reporting administration information system that uses the waterfall model as a software development model consisting of analysis, design, coding, testing. and supporters. Data collection techniques used consisted of observation, interviews and literature study. This system provides facilities to two (2) levels of users, namely Secretariat officers and SKPD officers. Secretariat officers can manage SKPD data, users, descriptions, programs, activities, access RKA-SKPD reports and realization reports. SKPD officers can change SKPD data, manage users, manage RKA-SKPD, access RKA-SKPD reports (personal), manage realization transactions and access realization reports (personal). This system is made using hypertext preprocessor (PHP) programming language, hypertext markup language (HTML), cascading style sheet (CSS), jquery, javascript and bootstrap as well as codeigniter as a framework, MySQL as a database application and sublime text as a web editor. This system is expected to help and be used as a tool in the administration of reporting on the realization of SKPD at BAPPEDA Kubu Raya Regency